Mooring system diagnosis and structural reliability control for position moored vessels. (March 2015) - Fang, Shaoji; Blanke, Mogens; Leira, Bernt J.
Abstract: Early diagnosis and fault-tolerant control are essential for safe operation of floating platforms where mooring systems maintain vessel position and must withstand environmental loads. This paper considers two critical faults, line breakage and loss of a buoyancy element and employs vector statistical change detection for timely diagnosis of faults. Diagnosis design is scrutinised and a procedure is proposed based on specified false alarm probability and estimation of the distribution of the test statistics on which change detection is based. A structural reliability index is applied for monitoring the safety level of each mooring line and a set-point chasing algorithm accommodates the effects of line failure, as an integral part of the reliability-based set-point chasing control algorithm. The feasibility of the diagnosis and of the fault-tolerant control strategy is verified in model basin tests. Abstract : Highlights: Fault diagnosis and fault tolerant control are demonstrated for a Floating Production Storage and Offloading (FPSO) vessel. Risk of line breakage is employed to calculate the actions needed to protect mooring lines from cascaded breakage. The approach is shown to enhance operational safety after breakage of a line or loss of a buoyancy element. Model basin test results validate the combined diagnosis and fault tolerant set-point chasing control.